Advances in Stroke: Therapies Targeting Stroke Recovery. Issue 1 (January 2021) - Richards, Lorie G.; Cramer, Steven C.
Abstract : Stroke recovery therapies promote favorable neural plasticity, both during spontaneous recovery and the chronic phase. Activity-based therapies based on intense practice, some aided by integration of computers and telehealth, have shown promise. These studies emphasize key therapeutic variables such as dose, intensity, and timing. Preclinical drug studies have shown promise, but human translation has been challenged by identifying the target patient subgroup, requirements for concomitant training, and aligning biomarkers with preclinical evidence.